Arene-Ruthenium(II) Complexes with Carbothiamidopyrazoles as a Potential Alternative for Antibiotic Resistance in Human - Ewelina Namiecińska; Magdalena Grazul; Beata Sadowska; Marzena Więckowska-Szakiel; Paweł Hikisz; Beata Pasternak; Elzbieta Budzisz (Molecules, 2022)
To meet the demand for alternatives to commonly used antibiotics, this paper evaluates the antimicrobial potential of arene-ruthenium(II) complexes and their salts, which may be of value in antibacterial treatment. Their antimicrobial activity (MIC, MBC/MFC) was examined in vitro against Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus faecalis, Pseudomonas aeruginosa, Proteus vulgaris and Candida albicans and compared with classic antibiotics used as therapeutics. Selected arene-ruthenium(II) complexes were found to have synergistic effects with oxacillin and vancomycin against staphylococci. Their bactericidal effect was found to be associated with cell lysis and the ability to cut microbial DNA. To confirm the safety of the tested arene-ruthenium(II) complexes in vivo, their cytotoxicity was also investigated against normal human foreskin fibroblasts (HFF-1). In addition, the antioxidant and thus pro-health potential of the compounds, i.e., their nonenzymatic antioxidant capacity (NEAC), was determined by two different methods: ferric-TPTZ complex and DPPH assay.